Experimental Research on Gifted Students and Social Media Communication Competence Program - Naif Kara; Kadriye Kobak; Aslı İgit (Journal of Economy Culture and Society)
The aim of this research was to develop a program to increase the social media communication competence levels of gifted students and to examine the effectiveness of the program. A 4- session program was developed within the scope of the research. The developed program was named SOMCOPGIS (Social Media Communication Competence Program for Gifted Students). A total of 32 experimental and control groups were formed using a random assignment method. The groups consisted of adolescent volunteers between the ages of 13 and 18 who all had low social media proficiency levels. In the data analysis non-parametric Friedman, Mann Whitney U tests, Social Media Competence Scale and analysis methods were used. Differences were found between the gifted students who participated in the SOMCOPGIS program and those who did not. It was observed that there was no significant difference in the social media competence scale scores of the adolescents in the control group obtained with the pre-test, post-test and follow-up test scales. This shows that SOMCOPGIS increased the social media communication proficiency level of the adolescents in the experimental group. This increase was found to be permanent with the follow-up test.